6 - African Development and the Primacy of Mental Decolonization: par Messay Kebede - Kebede , Messay (Africa Development, 2004)
The drastic and manifold difficulties Africa faces suggest that something more than mere delay, unfavorable conditions or misguided policies is obstructing the goal of development. The suggestion calls for a serious reflection on the experience of colonialism, but in a way different from those studies tracing African predicaments back to colonial or imperialist misdeeds. This does not mean colonialism is not the real culprit, just that such a stance is necessary in light of the fact that many studies have not focused on the real source of Africa's ills: the phenomenon of mental colonization. Those scholars who bring out the detrimental impact of mental alienation either fail to totally emancipate their views from Western constructs, or cannot produce an alternative to Eurocentrism. This paper discusses the contributions of African philosophical debates to the elucidation of the negative impacts of colonial discourse on Africa's development effort, ft draws attention to the limitations of the contributions and proposes an alternative conception vindicating the view that the great task of freeing the African mind from Eurocentric constructions takes priority over the design of development policies.